Design of an Electron Gun Using two Electrod Low Aberration Immersion Lens (Journal of the College of Education for Women, 2019)
Abstract A two electrode immersion electrostatic lens used in the designof an electron gun, with small aberration, has been designed usingthe finite element method (FEM). By choosing the appropriategeometrical shape of there electrodes the potential V(r,z) and theaxial potential distribution have been computed using the FEM tosolve Laplace's equation. The trajectory of the electron beam and the optical properties ofthis lens combination of electrodes have been computed underdifferent magnification conditions (Zero and infinite magnificationconditions) from studying the properties of the designed electrongun can be supplied with Abeam current of 5.7*10-6 A , electrongun with half acceptance angle of (5mrad)